Effects of Bacterial Inoculation to Immobilize Nickel in Wheat Grown on Ni-Contaminated Soil. Issue 1 (2nd January 2021) - Rasool, Atta; Ali, Salar; Ali, Waqar; Rehman, Atta Ur; Muhammad, Said
Abstract: Plant growth stimulating bacteria are very effective in immobilization of metals and reducing their translocation in plants through precipitation, and adsorption. A pot experiment was conducted to investigate the effectiveness of chitosan- and hematite-modified biochar and bacterial inoculations on the immobilization of nickel (Ni) in polluted soil under wheat cultivation. Application of modified biochars and inoculation with Pseudomonas putida significantly increased both wheat root and shoot dry matter yields but decreased Ni phytoextraction efficiency. The Ni concentration, translocation factor and uptake in wheat shoot and root significantly decreased the application of either modified or unmodified biochars. Bacterial inoculation significantly decreased mean translocation factor and also root and shoot concentration and the uptake Ni in the shoot. Chitosan-modified biochar was the most influential treatment in decreasing Ni uptake by wheat followed by P. putida inoculation treatment. The results demonstrated positive effects of chitosan modified biochar and inoculation with P. putida in increasing dry matter yield and decreasing Ni uptake in wheat grown on Ni-contaminated soil. According to the results of present study, modified biochars application and bacterial inoculation are influential treatments which prevent Ni toxicity probably.